Fundamentals of supply chain management twelve drivers of competitive advantage - Mentzer, John T.
This text introduces 12 'drivers' for success based on the author's extensive research and experience in consulting. The roles of all the traditional business functions in supply chain management - marketing, sales, logistics, etc. - are also addressed
Keywords: Business logistics; Strategic planning; Supply Chain Management; Wettbewerbsvorteil